Design, build and test of a planar biaxial tensile testing machine for skin and other collagenous soft tissues - Caine, Jonathan Andrew (Department of Mechanical Engineering, 2023)
This investigation forms part of a larger study, investigating the mechanical properties of skin and other soft membrane tissue. The focus of this project was the design and construction of a planar biaxial tensile testing machine, suitable for ultimately testing skin and other soft membrane tissues. The mechanical properties of skin and other collagenous soft tissues are of interest to a wide range of researchers and professionals. Interests include medical device design, research into the change in skin's mechanical properties due to disease, and skin's material characterisation for computational simulation. None of the laboratories at the University of Cape Town (UCT) were capable of performing planar biaxial tensile tests on soft tissue prior to this project. The machine was designed as a stand-alone, portable and accurate tensile tester with two independent and orthogonal testing axes. The machine was designed to be operated using GRBL software: an open-source motion control system for CNC milling. Two 50 N tensile load cells (K-S2M, Hottinger Baldwin Messtechnik, Darmstadt, Germany) were used for load measurement and a non-contact Digital Image Correlation (DIC) system (Dantec, Denmark) was used for three-dimensional surface displacement measurement. Commissioning testing was done on a silicone elastomer (Smooth-On, Dragon Skin 10) which was used as a skin surrogate. The commissioning testing did not seek to characterise the surrogate material, but to verify that the machine operated as intended. As testing of biological specimens will involve non-trivial specimen preparation and mounting, this is left to future research. Initially, a single axis of the custom machine was used to perform uniaxial tensile tests on the surrogate material. Specimens of the same surrogate material were tensile tested using a calibrated Instron (Norwood, MA, USA) tensile testing machine at the Centre for Materials Engineering (CME) at UCT for comparison. Twenty specimens were tested on each machine: five specimens per cross-head displacement rate: 10, 50, 120 and 400 mm/min. Sources of error were identified and addressed through minor design and procedure changes. Further uniaxial testing on the revised first axis, and the newly built second axis, was performed at 50 mm/min and 400 mm/min. These results compared favourably to the results from the Instron tensile testing machine. Planar biaxial tensile tests were performed on cruciform specimens of the surrogate silicone elastomer. Biaxial testing was performed at four different cross-head displacement rates (10, 50, 120 and 400 mm/min) combined with five different loading ratios between the axes (1:1, 1:0.75, 1:0.5, 1:0.25, 1:0). A total of 30 specimens were tested. The performance of the machine was critically assessed and the areas of difficulty encountered during testing were: handling and gripping the highly pliable specimens, consistency in the boundary conditions of the specimen, inter specimen variability, and alignment issues. The testing demonstrated that the machine functions as intended, and meets the requirements to be used in the testing of skin and other membrane tissue in the future.